Numerical investigation of the effectiveness of FRP and TRM in repairing corrosion damaged reinforced concrete beams - Moniruzzaman, P.K.M. (University of British Columbia, 2013)
In steel reinforced concrete (RC) structures, corrosion reduces the reinforcement cross-sectional area and causes cracking and/or spalling of the concrete cover. This will reduce the strength of the structure and may cause collapse. A certain degree of structural strength can be preserved and/or increased by using strengthening techniques. Fibre reinforced polymer (FRP) composite material has gotten approval in the rehabilitation engineering community for possessing superior mechanical properties in terms of resistance to corrosion, high strength to weight ratio and ease of installation. On the other hand, an efficient, sustainable and durable material, namely, textile reinforced mortar (TRM), has been introduced recently as a retrofitting material that maintains the positive characteristics of FRP while eliminating its drawbacks. Thus, to use this system in practical conditions it is necessary to evaluate its effectiveness and compare it with the FRP system. The current numerical study investigated the structural performance of corrosion damaged reinforced concrete beams repaired with externally bonded FRP and TRM systems. The studied parameters were the reinforcement ratio, the corrosion level and the existence and type of the strengthening system. Results showed that failure mode was initiated by steel yielding for all studied beams. The study found that the TRM/FRP system should be applied such that the strengthened beams would not be over-reinforced to prevent compression failure. In addition, for the given material properties, the TRM strengthened beams showed better performance with respect to stiffness compared to their FRP strengthened counterparts, while the FRP strengthened beams were better in terms of loading capacity, displacement and ductility behaviours except for beams having high tensile steel reinforcement ratio. In such case, the TRM strengthened beams showed almost equal effectiveness as the FRP ones. Given the scope of this study, it is suggested that the full strength of the FRP and TRM systems could be achieved if the unstrengthen beam have tensile steel reinforcement ratio less than 24% and 73% of its balanced reinforcement ratio, respectively. === Applied Science, Faculty of === Engineering, School of (Okanagan) === Graduate